Isolated increase of plasma glucose levels at 30 minutes during oral glucose tolerance test (OGTT) in young adult patients with transfusion-dependent β-thalassemia (β-TDT): A possible predictor marker for early development of glucose dysregulation (GD) - De Sanctis, Vincenzo; Soliman, Ashraf; Daar, Shahina; Tzoulis, Ploutarchos; Kattamis, Christos (Acta Biomedica Atenei Parmensis, 2025)
Background: In the general population, prospective studies have documented that intermediate plasma glucose (PG) at 30-min or 1- hour during a standard oral glucose tolerance test (OGTT) are associated with a high risk of glucose dysregulation (GD) and incidence of diabetes. Study aims: The main aim of this retrospective observational study was to determine whether high 30-min-PG levels could be an early indicator of GD in β-TDT patients with an otherwise normal glucose tolerance test (NGT). Patients and Methods: A total of 57 β-TDT young adult patients with normal OGTT were re-evaluated, according to the American Diabetes Association guidelines. Indices of insulin secretion and sensitivity were also calculated. Patients were divided into 3 groups (A, B and C), according to 30-min PG evaluated in percentile. Results: At last consultation, the number of patients with GD was significantly higher in Group C vs. Group A (12/19 vs. 5/19; P: 0.048). In addition, in Group A, an attenuated mean oral disposition index (oDI30) was observed, suggesting impairment of glucose metabolism. In Group B and Group C, a significant inverse correlation between the insulinogenic index (IGI) vs 2-h PG (r = -0.3480; P = 0.037) and a significant positive correlation between IGI and oDI30 were documented (r = 0.7727; P: < 0.00001). Conclusions: Young adult β-TDT subjects with NGT and isolated high 30-min PG > 75th percentile (≥155 mg/dL) may represent a distinct group of patients at a risk for developing GD, likely due to decreased insulin sensitivity and pancreatic β-cell dysfunction.